Contemporary Arab women's life writing and the politics of resistance - Cheurfa, Hiyem (Edinburgh : Edinburgh University Press, 2023)
Explores the relationship between revolutionary movements and experimental life writing forms by contemporary Arab women.
4 Dissident Laughter: Diaries of National Struggles and the Aesthetics of Humour -- 5 Arab Women's Digital Life Writing: Resistance 2.0 -- Conclusion -- Arab(ic) Resistance Non-fiction: Critical Trajectories -- Bibliography -- Index
Includes bibliographical references and index.
Description based on print version record.
In English.
JSTOR
Keywords: Arabic literature -- Women authors -- History and criticism; Women -- Political activity -- Arab countries; Arabic literature -- Women authors; Women -- Political activity; Arab countries; LITERARY CRITICISM / Middle Eastern; Electronic books; Criticism, interpretation, etc